Remaking history. / Volume 1, Early makers - Gurstelle, William, ....- (San Francisco : Maker Media, 2016)
William Gurstelle begins his remarkable journey through history with this volume, Early Makers. Each chapter examines a remarkable individual or group of people from the past whose insights and inventions helped create the world we live in. What sets this series apart from other history books - including other histories of technology - is that each chapter also includes step-by-step instructions for making your own version of the historical invention. History comes to life in a way you have never experienced before when you follow the inventors' steps and recreate the groundbreaking devices of the past with your own hands.
Keywords: Technology -- History; Industrial arts -- History; Inventions -- History; Inventors -- History